Relationship Between Occupational Safety Services and Emergency Response Management Development of Nurse Performance - Najihah, Khoirotun; Salmira, Cut Saura; Apriani, Nurlia; Hasibuan, Sindy Syaputri (Jurnal Perilaku Kesehatan Terpadu, 2023)
Because the hospital has a huge workface with a significant risk of occupational illnesses or work accidents, it is required to take safeguards, such as adopting work safety services and building emergency response management. Hospitals face a range of complex labor concerns, including varying risks of occupational disease and even work-related accidents depending on the kind of employment, thus they are required to adopt initiatives to promote Hospital Occupational Health and Safety (K3RS). Therefore, it is necessary to provide work safety services and develop emergency response management in hospital so that work accidents and occupational diseases can be prevented. This Study aims to determine the relationship between occupational safety services and development emergency response management with workface performance at special eye hospital medan Baru in 2022 with a cross sectional approach.